Cellular Immune Response in Horses After West Nile Neuroinvasive Disease - Tolnai, Csenge; O’Sullivan, Ciara; Lőrincz, Márta; Karvouni, Maria; Tenk, Miklós; Marosi, András; Forgách, Petra; Paszerbovics, Bettina; Wagenhoffer, Zsombor; Kutasi, Orsolya (Animals (Basel), 2025)
West Nile virus (WNV) is a mosquito-borne neurotropic virus that causes neurologic disease in both humans and horses. Yet the long-term cellular immune response following natural infection in horses remains poorly understood. This study aims to evaluate the WNV-specific T-cell response in horses recovered from West Nile neuroinvasive disease (WNND). Twelve client-owned horses (4 Hungarian sport horses, 2 Lippizaners, 1 KWPN, 1 Shagya Arabian, 1 Friesian, 1 Gidran, 1 Andalusian, and 1 draft cross horse) with confirmed clinical WNV infection were enrolled, and peripheral blood mononuclear cells (PBMCs) were collected approximately 290 days post infection. An equine interferon-gamma (IFNγ) Enzyme-Linked Immunospot (ELISpot) assay was performed using a WNV capsid peptide pool as an antigen to assess virus-specific cellular immunity. Results: Ten of twelve horses (83%) exhibited a significant IFNγ response. Statistical analyses revealed no association between ELISpot responses and clinical severity, age, sex, breed, or neutralizing antibody titers. These results demonstrate that naturally infected horses are capable of mounting robust WNV-specific T-cell responses independent of humoral immunity. The findings support a potentially important role for cellular immune memory in long-term protection against WNV reinfection and suggest that the capsid peptide-based ELISpot assay may serve as a useful diagnostic or research tool for the evaluation of orthoflavivirus immunity in equines.